Validation of controllers for photovoltaic inverters using automated tests and hardware-in-the-loop - João V. L. Rosa; Luiz F. R. Menegazzo; Lucas V. Belinaso; Fernanda de M. Carnielutti; Humberto Pinheiro (Eletrônica de Potência)
The ABNT NBR-16149 and NBR-16150 standards and INMETRO Ordinance No. 140 establish requirements for connecting PV inverters to the Brazilian electrical grid. To meet these requirements, the firmware of these devices needs to be properly designed and validated. Additionally, it is important to perform tests to verify whether the inverter and its control systems comply with the standards. In this context, this paper presents a methodology for the validation of controllers for PV inverters using Hardware-in-the-loop (HIL). To validate the proposed methodology, a two-level three-phase PV inverter with Finite Control Set Model Predictive Control (FCS-MPC) for current control and additional control and grid connection functionalities was evaluated. The compliance of the controller with relevant standards was assessed through automated HIL testing. This approach allows control designers to identify potential issues in advance, refine algorithms, and enhance controller performance before the complete hardware certification process of the inverter.